THE INTEGRITY OF AUDITORS IN ISLAMIC PERSPECTIVE A COMPARATIVE STUDY WITH THE LEADERSHIP OF UMAR IBN AL-KHATTAB - Fika Hartina Sari; Melsa Jumliana; Nur Asmi Ainun Kamal; Siska Armalivia; Rahadian Cahyadi (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
This research aims to explore the alignment between the principles of professional auditor ethics and the spiritual and moral values exemplified in Islam. It employs a qualitative approach, utilizing library research methods. Data were collected through a literature review, including the Qur'an, hadith, biographies of Umar ibn Khattab, and Islamic guidelines on auditor ethics. The analysis was conducted using a descriptive-comparative method to identify similarities and differences between the principles of auditor integrity and Islamic leadership values. The findings indicate that auditor integrity in Islam encompasses the values of trustworthiness (amanah), honesty (sidq), justice (adl), consistency (istiqamah), and piety (taqwa). These values are prominently reflected in the leadership of Umar ibn Khattab, who prioritized justice, transparency, accountability, and public oversight. There is a strong alignment between auditor integrity and the leadership principles of Umar, both of which are deeply rooted in Islamic teachings (Sharia). This study contributes to strengthening the professional ethics of Muslim auditors by emphasizing the importance of spiritual values in upholding integrity. The findings also provide a foundation for developing audit policies based on Islamic values and offer ethical, morally driven leadership inspiration for contemporary auditing practices.